Role of nutraceuticals in human health - Das, Lipi (Springer-Verlag, 2011)
Nutraceutical is the hybrid of ‘nutrition’ and ‘pharmaceutical’. Nutraceuticals, in broad, are food or part of food playing a significant role in modifying and maintaining normal physiological function that maintains healthy human beings. The principal reasons for the growth of the nutraceutical market worldwide are the current population and the health trends. The food products used as nutraceuticals can be categorized as dietary fibre, prebiotics, probiotics, polyunsaturated fatty acids, antioxidants and other different types of herbal/ natural foods. These nutraceuticals help in combating some of the major health problems of the century such as obesity, cardiovascular diseases, cancer, osteoporosis, arthritis, diabetes, cholesterol etc. In whole, ‘nutraceutical’ has lead to the new era of medicine and health, in which the food industry has become a research oriented sector.